2009
DOI: 10.1128/jb.00830-08
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Importance of Transmembrane Domain 3 (TM3) in the Aspartate:Alanine Antiporter AspT: Topology and Function of the Residues of TM3 and Oligomerization of AspT

Abstract: AspT, the aspartate:alanine antiporter of Tetragenococcus halophilus, a membrane protein of 543 amino acids with 10 putative transmembrane (TM) helices, is the prototype of the aspartate:alanine exchanger (AAE) family of transporters. Because TM3 (isoleucine 64 to methionine 85) has many amino acid residues that are conserved among members of the AAE family and because TM3 contains two charged residues and four polar residues, it is thought to be located near (or to form part of) the substrate translocation pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 53 publications
(50 reference statements)
1
37
0
Order By: Relevance
“…Nanatani et al (14) established AspT purification and reconstitution methods and confirmed L-aspartate self-exchange properties. Here, we clearly demonstrated that purified AspT alone is sufficient for the electrogenic Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nanatani et al (14) established AspT purification and reconstitution methods and confirmed L-aspartate self-exchange properties. Here, we clearly demonstrated that purified AspT alone is sufficient for the electrogenic Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The solubilized AspT was incubated with L-aspartate (5, 10, and 20 mM) or L-alanine (50, 100, and 200 mM) at 37°C for several minutes. After the reconstitution, the remaining transport activities of AspT reconstituted into proteoliposomes loaded with 200 mM L-alanine and 50 mM N-methyl-D-glucamine-phosphate (pH 7.0) were examined by using a simple filtration method (14).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations